Peel bond strength of resilient liner modified by the addition of antimicrobial agents to denture base acrylic resin - Alcantara, Cristiane S.; de Macedo, Allana F. C.; Gurgel, Bruno C. V.; Jorge, Janaina Habib [UNESP]; Neppelenbroek, Karin H.; Urban, Vanessa M. (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2012)
In order to prolong the clinical longevity of resilient denture relining materials and reduce plaque accumulation, incorporation of antimicrobial agents into these materials has been proposed. However, this addition may affect their properties. Objective: This study evaluated the effect of the addition of antimicrobial agents into one soft liner (Soft Confort, Dencril) on its peel bond strength to one denture base (QC 20, Dentsply). Material and Methods: Acrylic specimens (n=9) were made (75x10x3 mm) and stored in distilled water at 37 degrees C for 48 h. The drug powder concentrations (nystatin 500,000U - G2; nystatin 1,000,000U - G3; miconazole 125 mg - G4; miconazole 250 mg - G5; ketoconazole 100 mg - G6; ketoconazole 200 mg - G7; chlorhexidine diacetate 5% - G8; and 10% chlorhexidine diacetate - G9) were blended with the soft liner powder before the addition of the soft liner liquid. A group (G1) without any drug incorporation was used as control. Specimens (n=9) (75x10x6 mm) were plasticized according to the manufacturers' instructions and stored in distilled water at 37 degrees C for 24 h. Relined specimens were then submitted to a 180-degree peel test at a crosshead speed of 10 mm/min. Data (MPa) were analyzed by analysis of variance (alpha=0.05) and the failure modes were visually classified. Results: No significant difference was found among experimental groups (p=0.148). Cohesive failure located within the resilient material was predominantly observed in all tested groups. Conclusions: Peel bond strength between the denture base and the modified soft liner was not affected by the addition of antimicrobial agents.
Keywords: Antifungal agents; Tensile strength; Stomatitis; Denture bases